2013
DOI: 10.1530/eje-12-0656
|View full text |Cite
|
Sign up to set email alerts
|

ENDOCRINE DISORDERS IN CHILDHOOD AND ADOLESCENCE: Natural history of subclinical hypothyroidism in children and adolescents and potential effects of replacement therapy: a review

Abstract: Objective: Subclinical hypothyroidism (SH) is quite common in children and adolescents. The natural history of this condition and the potential effects of replacement therapy need to be known to properly manage SH. The aim of this review is to analyze: i) the spontaneous evolution of SH, in terms of the rate of reversion to euthyroidism, the persistence of SH, or the progression to over hypothyroidism; and ii) the effects of replacement therapy, with respect to auxological data, thyroid volume, and neuropsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
5

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 59 publications
4
72
1
5
Order By: Relevance
“…Only few studies have evaluated the effect of shortterm trials with L-T4 in heterogeneous populations of children with mild to severe SH (5,20,23), and none of them have focused on the relationship between SH and metabolic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Only few studies have evaluated the effect of shortterm trials with L-T4 in heterogeneous populations of children with mild to severe SH (5,20,23), and none of them have focused on the relationship between SH and metabolic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…In childhood, this is an even more controversial issue (6,7,8,9,10) and the only available study comparing the effects of L-T 4 treatment vs no therapy in idiopathic SH suggests that therapy is unable to modify post-therapy outcome of hyperthyrotropinemia and to prevent the risks of a subsequent TSH increase after treatment withdrawal (11). In the children with HT-related mild SH, it has been just recently reported that the evolution of thyroid function tests seems to be frequently characterized by a deterioration over time, whereas such risk is very low in the children with idiopathic SH (12).…”
Section: Introductionmentioning
confidence: 99%
“…For subclinical hypothyroidism, there are only a few studies in children/adolescents, and it appears that thyroxine treatment leads to increased growth (29). Our finding of a relation between rs4704397 SNP and body height is therefore plausible.…”
Section: Jorde Et Almentioning
confidence: 58%